Perkembangan Sistem Pendidkan di Negara Myanmar - Dewi Sartika Hasibuan; Mislaini Mislaini; Siti Kholijah Harahap (BADAN PENERBIT STIEPARI PRESS, 2025)
This article examines the history of the development of the education system in Myanmar, from the pre-colonial era to the modern era. Myanmar has an education system influenced by Buddhist monasteries and British colonialism. The current education system covers elementary to high levels which is managed by the government. However, discrimination against minority groups, particularly Muslims, as well as infrastructure and policy challenges, hinder educational equity. This article also discusses the curriculum structure, levels of education, and the main challenges in equitable education in Myanmar.